1999
DOI: 10.1007/s004030050451
|View full text |Cite
|
Sign up to set email alerts
|

Alginate oligosaccharides stimulate VEGF-mediated growth and migration of human endothelial cells

Abstract: Alginate oligosaccharides cleaved from alginic acid polysaccharides of seaweed were tested to determine their ability to enhance proliferation and migration of human umbilical vein endothelial cells. A mixture of alginate oligosaccharides (5 microg/ml in culture broth) stimulated endothelial cell growth, [(3)H]thymidine uptake and migration in the presence of recombinant vascular endothelial growth factor 165 (VEGF(165)). In contrast, a high concentration mixture of the oligosaccharides ( approximately 100 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 30 publications
2
59
0
Order By: Relevance
“…To our knowledge, this is the first report that ascophyllan or even algal-derived sulfated polysaccharides can promote the growth of certain cell lines under normal growth conditions. Regarding the effects of saccharides on the growth of certain mammalian cells, it has been reported that alginate oligosaccharides stimulate or enhance vascular endothelial growth factor-mediated growth of human endothelial cells and the growth of keratinocyte in the presence of epidermal growth factor (32,33). Since no significant effects of alginate oligosaccharides were observed on the cells in the absence of the growth factors, it has been considered that alginate oligosaccharides may stimulate proliferative activity of growth factors by a synergistic mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is the first report that ascophyllan or even algal-derived sulfated polysaccharides can promote the growth of certain cell lines under normal growth conditions. Regarding the effects of saccharides on the growth of certain mammalian cells, it has been reported that alginate oligosaccharides stimulate or enhance vascular endothelial growth factor-mediated growth of human endothelial cells and the growth of keratinocyte in the presence of epidermal growth factor (32,33). Since no significant effects of alginate oligosaccharides were observed on the cells in the absence of the growth factors, it has been considered that alginate oligosaccharides may stimulate proliferative activity of growth factors by a synergistic mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Strain 168 RG lyases, especially YesX, release the unsaturated RG disaccharide from substrates. Oligosaccharides called oligosaccharins show physiological functions such as a bifidus factor, an elicitor of plant growth, a growth enhancer of human endothelial cells and keratinocytes, and an inducer of cytokine production from mouse macrophage cells (1,5,18,19,21,22,27). The unsaturated RG disaccharide "lepidimoide" has been isolated from seeds of cress (Lepidium sativum L.) and shown to function as an allelopathic factor for plants (12,53).…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Most recently, wobble oligosaccharide motifs of chondroitin sulfate/dermatan sulfate proteoglycans had been demonstrated to induce signaling pathways that are essential for the proliferation, self-renewal, and cell lineage commitment of neural stem cells. 58 Although stiff alginate hydrogels were described as an inert matrix, alginate-derived oligosaccharides have been reported to costimulate growth factormediated proliferation, migration, and adhesion of endothelial cells, keratinocytes, and skin fibroblasts in vitro; [59][60][61] cytokine production by RAW264.7 cells; 62 and phagocytic activity of peritoneal monocytes. 63 The density of substrateimmobilized signaling molecules is crucial to initiate extracellular signaling events that lead to cell differentiation, adhesion, growth, and migration, and this must be considered during scaffold designing.…”
mentioning
confidence: 99%